Cele klimatyczne w działalności przedsiębiorców publicznych: aspekty prawne - Bojar-Fijałkowski, Tomasz (PRAWO i WIĘŹ, 2025)
State Treasury sets objectives for the companies it supervises. These can, and should, include economic goals, but also social goals, including environmental ones. This paper points to this possibility, justifies such a need on the basis of European Union law and public climate policies, and indicates the instruments for doing so. The paper begins by defining supervision and the objectives in supervision, taking into account the doctrine of administrative law. It goes on to identify the current regulations on management objectives in public companies and their wording. The next parts of the thesis deal with the role of the environment in European Union policies and law, particularly within the framework of the „European Green Deal”, and the role of the environment in market practices and private financing. The last part of the argument is an analysis of the possibility and legitimacy of including environmental objectives in the corporate governance of public companies in Poland. The whole is ended with conclusions and a list of sources.